Effective Trade Costs and the Current Account : An Empirical Analysis - Boz, Emine; Li, Nan.; Zhang, Hongrui (Washington, D.C. : International Monetary Fund, 2019)
A view receiving increased support is that the height of trade costs in prime export sectors has a strong effect on current account balances: countries specializing in sectors that face relatively high trade costs, such as services, tend to run current account deficits, and similarly, countries specializing in low trade cost sectors, such as manufacturing, tend to run current account surpluses. To test this view, we first infer comparative advantages and trade costs, by sector, within a large sample of countries for the period 1970-2014. Then we construct effective trade costs-trade costs weighted by sectoral comparative advantage-to gauge the height of a country's overall trade costs. Results reveal that, although higher effective exporting costs are associated with lower current account balances, their impact is quantitatively limited; furthermore, the effective costs of importing often have no statistically significant effect.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet